Concern and Risk Perception: Effects on Osteoprotective Behaviour - A. L. Barcenilla-Wong; J. S. Chen; L. M. March (Journal of Osteoporosis)
This study aimed to determine the effect that level of concern for osteoporosis, as well as self-perceived risk of osteoporosis and fracture, has on supplementation use, seeking medical advice, bone mineral density (BMD) testing, and antiosteoporosis medication (AOM) use. Study subjects were 1,095 female Australian participants of the Global Longitudinal study of Osteoporosis in Women (GLOW) untreated for osteoporosis at baseline. Study outcomes from self-administered questionnaires included calcium and vitamin D supplementation, self-reported seeking of medical advice regarding osteoporosis, BMD testing, and AOM use in the last 12 months at the late assessment. Logistic regression was used in the analysis. Concern significantly increased the likelihood of seeking medical advice and, however, had no significant impact on screening or treatment. Heightened self-perceived risks of osteoporosis and fracture both significantly increased the likelihood of seeking medical advice and BMD testing while elevated self-perceived risk of fracture increased AOM use. Supplementation use was not significantly associated with concern levels and risk perception. Concern and risk perceptions to osteoporosis and fracture were significantly associated with certain bone-protective behaviours. However, the disconnect between perceived osteoporosis risk and AOM use illustrates the need to emphasize the connection between osteoporosis and fracture in future education programs.